Assessment of Yield and Drought Tolerance in Iranian Sainfoin Cultivars - S. Irani; M. M. Majidi; A. Mirlohi (Tulīd va Farāvarī-i Maḥṣūlāt-i Zirā̒ī va Bāghī, 2016)
This research was conducted to evaluate 30 sainfoin cultivars in terms of yield, agronomic and morphological traits under water stress condition, using different drought tolerannce indices. A randomized complete block design with three replications was employed during two years at Isfahan University of Technology Research Farm, Isfahan, Iran. Effect of cultivars were significant for all of the measured traits at p<0.01. Also, the interactions of cultivars by moisture environment were significant for number of days to 50% flowering; inflorescence length, fresh and dry matter yield and leaf to stem ratio, indicating that different genotypes had different responses to moisture environments. Among different drought tolerance and susceptibility indices STI, GMP and MP had high correlation coefficients with yield under stress and non stress conditions, indicating that these indices are more suitable as criterion for selection of drought-tolerant cultivars. According to the studied indices and principle component analysis, cultivars 16 (Bardsir), 21 (Fereydunshahr 2), 23 (Najafabad 2) and 27 (Borujerd) were found to be the most desirable ones and can be considered as drought tolerant genotypes for future studies.